Pendampingan Literasi Digital dalam Pengembangan Wirausaha Warga RT 03 RW 04 Kelurahan Tunjungsekar Kecamatan Lowokwaru Kota Malang - Lestari, Ida Puji; Tusita, Arcci; Juliati, Juliati (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
Abstract Digital literacy refers to a person's ability to use digital technology effectively, including an understanding of how the technology functions, the ability to evaluate and understand digital information, and skills in interacting with digital devices and platforms for specific purposes such as communication, information retrieval, and content creation. This includes an understanding of the basic concepts of digital technology, online security, copyright, data privacy, as well as the ability to solve problems and adapt to rapid technological developments. Digital literacy has become increasingly important in today's digital era where digital technology permeates almost every aspect of daily life and is key to participating effectively in a technology-driven society and economy. Digital literacy assistance in developing entrepreneurship is a followup to the training given to residents of Tunjungsekar Subdistrict. From the team's observations, the residents in RT 03 RW 04, Tunjungsekar Village, still needs assistance after training was held for its members. The lack of training activities encouraged the team to carry out service activities. It is hoped that by providing digital literacy assistance in entrepreneurship, their knowledge and enthusiasm for opening a business will increase, so that they can help improve the economy/welfare of their families.